Antifungal activity and gene expression of lipopeptide antibiotics in strains of genus Bacillus - Grabova, A.Yu.; Dragovoz, I.V.; Zelena, L.B.; Tkachuk, D.M.; Avdeeva, L.V. (Вiopolymers and Cell, 2016)
Aim. To research the antifungal activity and gene expression of lipopeptide antibiotics in strains of genus Bacillus. Methods. Deferred antagonism method, PCR, qRT-PCR, MALDI-TOF mass spectrometry. Results. It was revealed that Bacillus sp. strains C6 and Lg37s out of five tested strains had the highest antifungal activity. Based on the molecular genetic methods, it was shown that the expression of genes of lipopeptide antibiotics, related to the fengycin family, occurred in all these strains. At the same time, the gene expression of cyclolipopeptide iturin was found in the Bacillus sp. strains C6 and Lg37s. It was determined that Bacillus sp. C6 strain had the highest level of expression of the fengycin operon`s genes, whereas the lowest level was observed in Bacillus sp. C10 strain. By means of MALDI-TOF mass spectrometry, the presence of fengycins in the cell-free cultural fluid of Bacillus sp. C6 strain was detected. Conclusion. The direct correlation between the level of antifungal activity and the fengycin synthetases expression has not been disclosed. A higher level of antagonism detected for two Bacillus strains is more likely associated with the expression and subsequent synthesis of fengycin and iturin.